1990
DOI: 10.1063/1.103275
|View full text |Cite
|
Sign up to set email alerts
|

Use of cathodoluminescence microscopy to distinguish semiconducting from metallic phases in high T c superconductors

Abstract: We show that semiconducting and insulating metal-oxide phases emit substantially greater luminescence when irradiated with 10–30 keV electrons than metallic, candidate high Tc superconducting phases. The use of a cathodoluminescence (CL) detector in a scanning electron microscope to form high-resolution CL images of Y2O3, BaCO3, Y2BaCuO5, oxygen-depleted YBa2Cu3O7−x(x>0.5), and oxygen-annealed YBa2Cu3O7−x(x∼0) is reported. The spatial resolution obtained in CL micrographs of YBa2Cu3O7−x is found to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…More recently, CL in the scanning electron microscope ͑SEM͒ has been used to characterize HTSC ceramics. Miller et al 7 observed that insulating phases in YBa 2 Cu 3 O 7Ϫx emit higher CL signals than nominally metallic phases, and other CL microscopy works indicated the relationship between certain luminescence features and oxygen-depleted zones in YBa 2 Cu 3 O 7Ϫx . [8][9][10][11] In particular a 2.3 eV emission band was related to centers involving oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, CL in the scanning electron microscope ͑SEM͒ has been used to characterize HTSC ceramics. Miller et al 7 observed that insulating phases in YBa 2 Cu 3 O 7Ϫx emit higher CL signals than nominally metallic phases, and other CL microscopy works indicated the relationship between certain luminescence features and oxygen-depleted zones in YBa 2 Cu 3 O 7Ϫx . [8][9][10][11] In particular a 2.3 eV emission band was related to centers involving oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 5 it was found that the total CL emission from oxygen-depleted YBa20.l307 x(x > 0.5) is consistently higher than that emitted by oxygen-annealed YBa2Cu307 _ xCx ~ 0). The role of oxygen in the luminescence emission of high Tc superconductors has also been pointed out in Ref.…”
mentioning
confidence: 93%
“…Since the mentioned treatments cause a variation in the oxygen stoichiometry or distribution, the possibility that the 540 nm luminescence is related to mechanisms in the oxygen sub-lattice has been investigated. Miller et al [14] reported an increase of CL signal in oxygen-depleted zones of YBCO produced by electron irradiation. Similar effects were reported in Refs.…”
Section: Introductionmentioning
confidence: 99%